2018
DOI: 10.1038/s41419-018-0617-7
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 suppresses diethylnitrosamine-induced hepatocyte death, compensatory proliferation and hepatocarcinogenesis through inhibiting p38 activation

Abstract: It is critical to understand the molecular mechanisms of hepatocarcinogenesis in order to prevent or treat hepatocellular carcinoma (HCC). The development of HCC is commonly associated with hepatocyte death and compensatory proliferation. However, the role of Caspase-3, a key apoptotic executor, in hepatocarcinogenesis is unknown. In this study, we used Caspase-3-deficient mice to examine the role of Caspase-3 in hepatocarcinogenesis in a chemical (diethylnitrosamine, DEN)-induced HCC model. We found that Casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Apoptosis-related genes strictly regulate cell apoptosis (34), in which Caspase is a cascade of cysteine-aspartic acid-specific proteases (35). The cascade pathway of cell apoptosis mediated by its protein family is activated by the action of multiple factors, and finally leads to cell apoptosis through a series of cascade reactions (36). Caspase-9 is the initiator of the Caspase cascade reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis-related genes strictly regulate cell apoptosis (34), in which Caspase is a cascade of cysteine-aspartic acid-specific proteases (35). The cascade pathway of cell apoptosis mediated by its protein family is activated by the action of multiple factors, and finally leads to cell apoptosis through a series of cascade reactions (36). Caspase-9 is the initiator of the Caspase cascade reaction.…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is highly upregulated in PLC, which is correlated with rapid progression from hepatitis to PLC [47]. Previous studies found that CASP3 (Caspase-3) can prevent chemical-induced PLC by suppressing p38 activation and hepatocyte death [48], and total flavonoids from Ampelopsis grossedentata (Teng cha) exerts an antitumor effect on PLC by upregulating the [49]. It is reported that PLC patients with high phosphorylated MAPK3 (also called ERK1) had significantly higher cancer recurrence and worse OS [50], and the impact of MAPK3 on survival was also verified by the survival curve in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It is directly or indirectly responsible for the cleavage of many proteins and caspases involved in apoptosis. 25 It is activated when cleaved into two protein fragments. Cleaved caspase-3 is responsible for the proteolytic cleavage of many critical proteins.…”
Section: Introductionmentioning
confidence: 99%